Pengembangan E-Instrumen Keterampilan Berpikir Kritis Berbasis Kearifan Lokal untuk Siswa Kelas VI SD - Jarwo Jarwo; Sumarno Sumarno; Joko Siswanto (Perkumpulan Kualitama Edukatika Indonesia, 2022)
Research and development of E-Instrument for Critical Thinking Skills Based on Local Wisdom for Grade VI Elementary School Students. The purpose of this development research is to describe the validity, practicality and effectiveness of E-Instrument Development of Critical Thinking Skills Based on Local Wisdom for Grade VI Elementary School Students. This research was conducted at SD Negeri Sempu, Limpung District, Batang Regency. Based on the results of the research on the Development of E-Instrument of Critical Thinking Skills Based on Local Wisdom for Grade VI Elementary School Students, which developed validation on the material aspects consisting of content, construction of local wisdom and language of assessment, an average score of 92.33% was obtained as a very feasible category. . The aspect of the completeness of the presentation which consists of 3 assessment points is obtained 3.7 with a percentage of 91.67% as a very feasible category. The Practicality of Developing E-Instruments for Critical Thinking Skills Based on Local Wisdom for Grade VI Elementary School Students is easy to use with a percentage of 96.25%. The learning outcomes obtained from the posttest results tested with the Independent Sample T-Test through the SPSS 16.0 program were stated to be sig. (2- tailed) is 0.000. This means that the assessment using E-Instruments is proven to be more effective in improving critical thinking skills.